A közép-európai közlemények körkérdései Közép-Európa történelméről. Első kérdés: felbomlás? összeomlás? szétzúzás? Avagy az Osztrák–Magyar Monarchia sorsa 1918 őszén - Gulyás, László (Közép-Európai Közlemények, 2018)
The publisher of the Central European Studies has been organizing conferences on the 20th century history of Europe since 2007; about 50 conferences were held. During these conferences we got the impression that Hungarian historians use scientific terms – termini technicus – rather loosely. Thus, in the present issue of our journal we launch a series of circular surveys among scientists concerning the proper use of different scientific terms. The series is entitled “Survey of the Central European Studies of the History of Central-Europe.” We hope that our initiative will generate fruitful professional disputes.